Citra Tradisi Sunda Dalam Persimpangan Budaya Kontemporer Sebagai Ide Penciptaan Seni Lukis - Solihah, Anggi; Setiadi, Gabriel Aries; Wahyudi, Nandang Gumelar (ATRAT: Jurnal Seni Rupa, 2024)
Sundanese traditions, which are rich in cultural and aesthetic values, are now at a cultural crossroads due to the influence of modernization and globalization. This creates challenges and opportunities for writers to maintain cultural identity while responding to changing times. The author observes and analyzes the current situation, this becomes the basic idea for the author to then express it into a painting. The author exploits cultural intersections to create work that not only maintains traditional values but is also relevant to contemporary issues. The process of creating paintings that combine traditional Sundanese imagery with contemporary cultural elements produces a meaningful form of artistic expression. In this way, it is hoped that this work can contribute to understanding cultural dynamics in painting and encourage more artists to explore and integrate traditional cultural heritage in their work.